2021
DOI: 10.1136/ejhpharm-2020-002669
|View full text |Cite
|
Sign up to set email alerts
|

Does timing matter on tocilizumab administration? Clinical, analytical and radiological outcomes in COVID-19

Abstract: Introduction While there are no pharmacological treatments with proven efficacy for coronavirus disease 2019 (COVID-19), tocilizumab has emerged as a candidate therapy. Some aspects of this therapy are still unknown, including the optimal timing of administration. Objective This observational study aimed to compare the 90-day mortality in two cohorts of patients when the drug was administered within the first 10 days from onset of symptoms or after day 11. Methods Patients hospitalised with severe COVID-19 pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…Since 30% received the drug more than 24 h after IMV onset, it is likely that late treatment had an impact on the outcome, although the optimal timing is yet to be proven 33 . A recently published observational study reported a lower 90-day mortality in patients that received tocilizumab within the first 10 days after symptom onset when compared with those that received the drug after day 11 34 . In our study, the prolonged time from admission to tocilizumab administration was due to low availability and high cost of the drug in our setting.…”
Section: Discussionmentioning
confidence: 96%
“…Since 30% received the drug more than 24 h after IMV onset, it is likely that late treatment had an impact on the outcome, although the optimal timing is yet to be proven 33 . A recently published observational study reported a lower 90-day mortality in patients that received tocilizumab within the first 10 days after symptom onset when compared with those that received the drug after day 11 34 . In our study, the prolonged time from admission to tocilizumab administration was due to low availability and high cost of the drug in our setting.…”
Section: Discussionmentioning
confidence: 96%
“…A meta‐analysis of six randomized controlled trials of COVID‐19 patients showed that tocilizumab was associated with a statistically significant reduction in the primary composite outcome of mechanical ventilation or 28‐day mortality 27 . The time‐course for achieving measurable improvement after tocilizumab in COVID‐19 has been reported as 5–6 days 28,29 …”
Section: Discussionmentioning
confidence: 99%
“… 27 The time‐course for achieving measurable improvement after tocilizumab in COVID‐19 has been reported as 5–6 days. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Moreno Diaz et al . [ 15 ] reported that the use of tocilizumab within 10 days of symptom onset is reported to significantly reduce the mortality at day 90 in severe COVID-19 cases. Although insignificant, we observed that in survivors, tocilizumab administration was a day earlier than in non-survivors.…”
Section: Discussionmentioning
confidence: 99%